2013
DOI: 10.1002/aenm.201201014
|View full text |Cite
|
Sign up to set email alerts
|

Application of Nanoparticle Antioxidants to Enable Hyperstable Chloroplasts for Solar Energy Harvesting

Abstract: The chloroplast contains densely stacked arrays of light‐harvesting proteins that harness solar energy with theoretical maximum glucose conversion efficiencies approaching 12%. Few studies have explored isolated chloroplasts as a renewable, abundant, and low cost source for solar energy harvesting. One impediment is that photoactive proteins within the chloroplast become photodamaged due to reactive oxygen species (ROS) generation. In vivo, chloroplasts reduce photodegradation by applying a self‐repair cycle t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
66
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 111 publications
(67 citation statements)
references
References 84 publications
1
66
0
Order By: Relevance
“…Previous studies demonstrated the potential of dextran-wrapped nanoceria as ROS scavengers for isolated chloroplasts 2 and microalgae 29 despite their inability to move through lipid bilayers and cell walls. According to our uptake mechanism, dextran-wrapped nanoceria do not interact with the chloroplast membrane owing to their neutral zeta potential 30 .…”
Section: Nanoparticle Spontaneous Assembly Within Chloroplastsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies demonstrated the potential of dextran-wrapped nanoceria as ROS scavengers for isolated chloroplasts 2 and microalgae 29 despite their inability to move through lipid bilayers and cell walls. According to our uptake mechanism, dextran-wrapped nanoceria do not interact with the chloroplast membrane owing to their neutral zeta potential 30 .…”
Section: Nanoparticle Spontaneous Assembly Within Chloroplastsmentioning
confidence: 99%
“…By capturing atmospheric CO 2 , these plant organelles convert light energy into three major forms of sugars that fuel plant growth: maltose, triose phosphate, and glucose 1 . Whereas photosystems interfaced with nanomaterials are extensively studied, nanoengineering chloroplast photosynthesis for enhancing solar energy harnessing remains unexplored 2 . One major deterrent in using chloroplast photosynthetic power as an alternative energy source is that these organelles are no longer independently living organisms.…”
mentioning
confidence: 99%
“…14 The chloroplast is responsible for CO 2 reduction to valuable and energy rich sugars and sugar precursors and as such has been extensively studied due to the potential to exploit plastome (genetic material of plastids) engineering for biotechnological applications, 15−17 as well as the potential for the chloroplast to serve as an engineering material. 18 Chloroplasts are similar to Gram-negative bacteria and mitochondria in that they are surrounded by two membranes, an outer membrane and an inner membrane. 19 Glycerolipids (galactolipids and sulfolipids) account for 52% of the total lipids in the outer membrane, while the inner membrane contains nearly 85% of glycerolipids such as Monogalactosyldiacylglycerol.…”
mentioning
confidence: 99%
“…SWCNTs have proven to be among the most versatile materials today, enabling a breadth of novel hybrid materials in fields spanning healthcare, 2−4 molecular biology, 5,6 energy, 7,8 and catalysis. 9 A large fraction of this recent research has focused on exploiting intrinsic SWCNT optical properties as a means of signal transduction in bio-optical devices.…”
Section: Introductionmentioning
confidence: 99%